Determination of the Relationship Between Voice and Swallowing Characteristics in Individuals aged 65 and Over with Sarcopenia Risk - Serkan Bengisu; Aynur İkra Demir (The Turkish Journal of Ear Nose and Throat)
Objective: Sarcopenia, which increases with age, causes a decrease in muscle mass and strength, potentially leading to changes in the voice’s acoustic, perceptual, and aerodynamic parameters, as well as dysphagia. This study aimed to assess the voice and swallowing functions of individuals aged 65 years at risk of sarcopenia and to explore the relationship between these functions.Method: Forty-nine participants who scored ≥4 on the Sarcopenia Risk Assessment Scale were included. Acoustic analysis was performed using the Multi-Dimensional Voice Programme (MDVP), and aerodynamic analysis included the maximum phonation time (MPT) and the s/z ratio. Swallowing was evaluated using the Swallowing Function Screening Test (EAT-10).Results: Participants were categorised into dysphagic (n=29) and non-dysphagic (n=20) groups based on their EAT-10 scores. Significant differences were found in several acoustic parameters, including fundamental frequency (F0), Shimmer, vAm, and FTRI (p=0.011, p=0.043, p=0.037, p=0.001). A significant difference in the SPI parameter was observed only in female participants (p=0.028). MPT showed significant differences between the dysphagic and non-dysphagic groups in both men and women (p=0.001, p=0.003, p=0.037). Positive correlations were found between EAT-10 and the acoustic parameters SPI and FTRI (p=0.031, p=0.048), while a negative correlation was found between MPT and EAT-10 (p=0.001).Conclusion: MPT was decreased in dysphagic individuals aged ≥65 years at risk of sarcopenia, and parameters related to decreased respiratory support and control, vocal cord closure, and airflow control during vocal cord adduction were negatively affected. These findings suggest that these parameters may be related to dysphagia risk factors in elderly individuals at risk of sarcopenia.